MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI TEMA 2 MENGGUNAKAN MODEL THINK PAIR SHARE - Fazriani, Siti (JURNAL SINEKTIK, 2023)
The background of this study is the low learning outcomes of theme 2 clean air for health which on average is below the KKM of 65. One of the contributing factors is that the learning strategies applied are not appropriate so that learning outcomes are low. The solution to this problem, the author applies the Think pair and share (TPS) model in the implementation of learning. The research data obtained at the meeting of 1 cycle I of 10 students, who obtained a score of â‰¥65, namely the meeting of 1 cycle I students who completed only 4 people or by 40%, then increased to 70% at meeting 2. Then at meeting 1 cycle II meeting 1 which is 80%. Thus the use of the Think pair and share (TPS) model is very effective and can improve the learning outcomes and abilities of grade V students of SDN Belitung Selatan 7 Banjarmasin.